Relevance of charged and polar amino acids for functionality of membrane toxin TisB - Leinberger, Florian H.; Berghoff, Bork A.; Justus Liebig University Giessen (My University, 2024)
Bacterial dormancy is marked by reduced cellular activity and the suspension of growth. It represents a valuable strategy to survive stressful conditions, as exemplified by the long-term tolerance towards antibiotics that is attributable to a fraction of dormant cells, so-called persisters. Here, we investigate the membrane toxin TisB (29 amino acids) from the chromosomal toxin-antitoxin system tisB/istR-1 in Escherichia coli. TisB depolarizes the inner membrane in response to DNA damage, which eventually promotes a stress-tolerant state of dormancy within a small fraction of the population. Using a plasmid-based system for moderate tisB expression and single amino acid substitutions, we dissect the importance of charged and polar amino acids. We observe that the central amino acids lysine 12 and glutamine 19 are of major importance for TisB functionality, which is further validated for lysine 12 in the native context upon treatment with the DNA-damaging antibiotic ciprofloxacin. Finally, we apply a library-based approach to test additional TisB variants in higher throughput, revealing that at least one positive charge at the C-terminus (either lysine 26 or 29) is mandatory for TisB-mediated dormancy. Our study provides insights into the molecular basis for TisB functionality and extends our understanding of bacterial membrane toxins.
Keywords: ddc:570